2020
DOI: 10.1038/s41598-020-74414-0
|View full text |Cite
|
Sign up to set email alerts
|

Roles of drinking and diet in the U-shaped relationship between smoking and BMI in middle-aged and elderly Chinese rural adults

Abstract: The study aimed to investigate the relationship between smoking and BMI, from the perspective of the roles of alcohol drinking and dietary factors in a rural population. We analysed cross-sectional data from 10,837 middle-aged and elderly Chinese rural adults who completed a questionnaire that included questions on demographic characteristics, dietary intake, and detailed smoking and drinking status. Results showed that current smokers had lower BMI and consumed foods less frequently (except coriander, onion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…At the same time, cigarette smoke induces an immune response and enhances type 2 in ammation, resulting in an increase in interleukin (IL)-4, IL-5 and IgE 29 , all of which contribute to an increased risk of asthma and exacerbation of asthma. In this study, we observed that pack-years were negatively correlated with BMI, possibly because smoking suppresses appetite, which is consistent with previous reports 30 . Interestingly, we also found that pack-years and years of smoking were negatively correlated with FeNO, IgE, blood eosinophils and blood neutrophils in the overall group.…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, cigarette smoke induces an immune response and enhances type 2 in ammation, resulting in an increase in interleukin (IL)-4, IL-5 and IgE 29 , all of which contribute to an increased risk of asthma and exacerbation of asthma. In this study, we observed that pack-years were negatively correlated with BMI, possibly because smoking suppresses appetite, which is consistent with previous reports 30 . Interestingly, we also found that pack-years and years of smoking were negatively correlated with FeNO, IgE, blood eosinophils and blood neutrophils in the overall group.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, dietary factors are well known to be highly related to BMI or body composition parameters 45 . Also, we could not classify the cholangiocarcinoma types (mass-forming, periductal-infiltrating and intraductal-growth) according to the Liver Cancer Study Group of Japan because it was not performed in our center 19 .…”
Section: Code De Champ Modifiémentioning
confidence: 99%
“…In addition, the D:A:D study demonstrated that diabetes risk among patients tested positive for HIV on ART increased linearly with increasing BMI ( 33 ). However, our research manifested that patients with overweight or obese had a higher risk of a high-increasing FPG trajectory than those with normal weight but had no statistically significant difference when compared with those underweight, presumably related to reverse causalities, such as a negative association between current smoking and BMI ( 34 ), which is an important contributor to the risk of diabetes ( 35 ). The association between baseline CD4 levels and different trajectories of FPG disappeared in the multivariable model.…”
Section: Discussionmentioning
confidence: 70%